PERANCANGAN DESAIN KEMASAN POTENSI WISATA KULINER DESA NAGREG KENDAN KABUPATEN BANDUNG - Nabila Azmi, Hanai; Denny Nugraha, Novian; Sri Soedew, Sri (Telkom University, 2024)
Nagreg Kendan Village is a village that is currently being developed to become a tourist destination. Besides its natural and cultural tourism potentials, Nagreg Kendan Village also has culinary tourism from several Micro, Small, and Medium Enterprises (MSME) actors that produce village flagship culinary products. However, the strategies to increase attractiveness and selling power of the culinary tourism potentials in the village are still minimal, so it is not widely known among the public, especially tourist. The packaging used mostly still uses simple packaging, does not yet display the visual identity of Nagreg Kendan Village and the characteristic of the product. The purpose of this research is to create packaging design to introduce it to public, especially tourist, increase attractiveness and selling power, as well as to become a characteristic of the culinary tourism potentials of Nagreg Kendan Village. The data collection methods used in compiling this final assignment report are: observation, interviews, and literature review. Keywords: Packaging design, Nagreg Kendan Village, Culinary tourism